Evaluating the Capacity of Human Gut Microorganisms to Colonize the Zebrafish Larvae (Danio rerio) - Valenzuela, Maria-Jose; Caruffo, Mario; Herrera, Yoani; Medina, Daniel A.; Coronado, Maximo; Feijóo, Carmen G.; Muñoz, Salomé; Garrido, Daniel; Troncoso, Miriam; Figueroa, Guillermo; Toro, Magaly; Reyes-Jara, Angelica; et al. (Frontiers in Microbiology, 2018)
In this study we evaluated if zebrafish larvae can be colonized by human gut microorganisms. We tested two strategies: 1) through transplantation of a human fecal microbiota and 2) by successively transplanting aerotolerant anaerobic microorganisms, similar to the colonization in the human intestine during early life. We used conventionally raised zebrafish larvae harboring their own aerobic microbiota to improve the colonization of anaerobic microorganisms. The results showed with the fecal transplant, that some members of the human gut microbiota were transferred to larvae. Bacillus, Roseburia, Prevotella, Oscillospira, one unclassified genus of the family Ruminococcaceae and Enterobacteriaceae were detected in 3 days post fertilization (dpf) larvae; however only Bacillus persisted to 7 dpf. Successive inoculation of Lactobacillus, Bifidobacterium and Clostridioides did not improve their colonization, compared to individual inoculation of each bacterium. Interestingly, the sporulating bacteria Bacillus clausii and Clostridioides difficile were the most persistent microorganisms. Their endospores persisted at least 5 days after inoculating 3 dpf larvae. However, when 5 dpf larvae were inoculated, the proportion of vegetative cells in larvae increased, revealing proliferation of the inoculated bacteria and better colonization of the host. In conclusion, these results suggest that it is feasible to colonize zebrafish larvae with some human bacteria, such as C. difficile and Bacillus and open an interesting area to study interactions between these microorganisms and the host.